2015
DOI: 10.7550/rmb.48028
|View full text |Cite
|
Sign up to set email alerts
|

Selected body temperature of nine species of Mexican horned lizards (Phrynosoma)

Abstract: Temperature plays an important role in the behavior, ecology, physiology, and evolution of reptiles. Herein, we present selected body temperatures on 9 species of Phrynosoma under laboratory conditions, and note congeneric differences related to altitude and reproductive mode. The results are discussed with those of other phrynosomatid lizards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Preferred body temperature at our study sites ( T set = 35.7 ± 0.33°C) was in between reported T set from other studies of Texas horned lizards (Table 1 ), but close to the average T set of 20 species of Phrynosomatids (35.1 ± 2.2°C; Clusella‐Trullas & Chown, 2014 ). Field body temperature ( T b = 33.6 ± 0.30°C) was similar to one reported value (33.4 ± 0.45°C; Lara‐Reséndiz, Arenas‐Moreno, et al, 2015 ) and lower than three other reported body temperatures for Texas horned lizards (35.7 ± ND °C, Brattstrom, 1965 ; 37.3 ± 0.30°C, Pianka & Parker, 1975 ; 35.2 ± 3.44 SD °C, Russell, 2001 ). Nonetheless, T b is lower than the mean environmental temperatures available to them ( T e = 35.2 ± 1.1°C) but falls within the lower T set25 range for lizards at our study sites.…”
Section: Discussionsupporting
confidence: 87%
“…Preferred body temperature at our study sites ( T set = 35.7 ± 0.33°C) was in between reported T set from other studies of Texas horned lizards (Table 1 ), but close to the average T set of 20 species of Phrynosomatids (35.1 ± 2.2°C; Clusella‐Trullas & Chown, 2014 ). Field body temperature ( T b = 33.6 ± 0.30°C) was similar to one reported value (33.4 ± 0.45°C; Lara‐Reséndiz, Arenas‐Moreno, et al, 2015 ) and lower than three other reported body temperatures for Texas horned lizards (35.7 ± ND °C, Brattstrom, 1965 ; 37.3 ± 0.30°C, Pianka & Parker, 1975 ; 35.2 ± 3.44 SD °C, Russell, 2001 ). Nonetheless, T b is lower than the mean environmental temperatures available to them ( T e = 35.2 ± 1.1°C) but falls within the lower T set25 range for lizards at our study sites.…”
Section: Discussionsupporting
confidence: 87%
“…Preferred body temperature at our study sites (T set = 35.7 +-0.33oC) was in between reportedT set from other studies of Texas horned lizards (Table 1), but close to the average T set of 20 species of Phrynosomatids (35.1 +-2.2oC;Clusella-Trullas and Chown 2014). Field body temperature (T b = 33.6 +-0.30oC) was similar to one reported value (33.4 +-0.45oC;Lara-Resendiz et al 2015b) and lower than three other reported body temperatures for Texas horned lizards (35.7 ± NDºC, Brattstrom 1965;37.3 ± 0.30ºC, Pianka and Parker 1975;35.2 ± 3.44 SDºC, Russell 2001). Nonetheless,T b is lower than the mean environmental temperatures available to them (T e = 35.2 ± 1.1ºC), but falls within the lower T set25 range for lizards at our study sites.…”
Section: Discussionsupporting
confidence: 86%
“…Lower thermal limits generally correlate with environmental conditions these species occupy (e.g. lower critical thermal minimum of species in cold regions; Campbell‐Staton et al., 2017; Lara‐Reséndiz et al., 2015). For example, if T emerg or VT max are lower in the northern than in southern populations, this would increase the time suitable to northern lizards for basking or foraging.…”
Section: Discussionmentioning
confidence: 99%
“…We used published data for the observed body temperature range of 23.8–40.2°C for active P. platyrhinos (Huey & Pianka, 2018), using the lower value for two behavioural thresholds, both temperature of emergence (T emerg ) and basking temperature (T bask ). Preferred temperature (T pref ) is the midpoint value of the range of selected temperatures recorded in a laboratory gradient (34.2°C; Lara‐Reséndiz et al., 2015) and indicates the temperature at which the lizard will begin seeking shade to maintain body temperatures within the voluntary thermal limits. Thermal limits required for the biophysical model are voluntary thermal minimum (VT min ) and maximum (VT max ), which are the range of body temperatures a lizard will tolerate before becoming inactive through behavioural modifications.…”
Section: Methodsmentioning
confidence: 99%